(untitled) (Itinera, 2016)
The paper focuses on the theory of art outlined by Giovanni Battista Montini (1897-1978) – usually known as Pope Paul VI (position held between 1963 and 1978) – investigated from an aesthetic point of view. The author refers also to less-known manuscripts outlined by G.B. Montini since the first decays of the XX century and then substantially confirmed by his subsequent speeches with the role of Archbishop of Milan (1954-1963) and later Pope. The paper allows to clarify the theoretical roots of the famous request addressed in 1964 to contemporary artists to enter into an alliance with the Church aimed at discovering the most genuine and spiritual needs of contemporary mankind. It focuses therefore not only on the Paul VI’s theory of holy art, but properly on his very conception of art and of the artists’ mission considered into a broader sense. The artist is ultimately regarded as a kind of prototype of contemporary Christian man.